2022
DOI: 10.2196/32922
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Independent Versus Laboratory-Based Stop-Signal Task Performance: Within-Subjects Counterbalanced Comparison Study

Abstract: Background Considered a facet of behavioral impulsivity, response inhibition facilitates adaptive and goal-directed behavior. It is often assessed using the Stop-Signal Task (SST), which is presented on stand-alone computers under controlled laboratory conditions. Sample size may consequently be a function of cost or time and sample diversity constrained to those willing or able to attend the laboratory. Statistical power and generalizability of results might, in turn, be impacted. Such limitations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…However, it is unknown whether remote administration had any effect on gSST performance, and it could be argued that the casual setting may have contributed to the rate of go-omission errors due to participant distraction. It is possible that the benefits may outweigh disadvantages, especially for those who tend to perform less well in pressured situations, and allow researchers to collect data from a wider, more representative sampling pool ( Assmann et al, 2016 ; Poulton et al, 2022 ). However, future research is required to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether remote administration had any effect on gSST performance, and it could be argued that the casual setting may have contributed to the rate of go-omission errors due to participant distraction. It is possible that the benefits may outweigh disadvantages, especially for those who tend to perform less well in pressured situations, and allow researchers to collect data from a wider, more representative sampling pool ( Assmann et al, 2016 ; Poulton et al, 2022 ). However, future research is required to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for the positive associations between motor impulsivity and conflict, withdrawal, and relapse may lie in the close relationship between motor impulsivity and response inhibition. Prior studies have shown that response inhibition is closely associated with motor impulsivity ( 96 , 97 ). Response inhibition refers to the ability to inhibit inappropriate or irrelevant responses, or resist temptations and resist acting impulsively so as to make flexible and goal-directed behavioral responses ( 98 , 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…The web-based SST consists of a practice block of 32 trials and three blocks of 64 experimental trials (Poulton, Chen, et al, 2022). A stop signal in the form of a white box surrounding the go stimuli appears on 25% of randomly selected trials.…”
Section: Stop-signal Task (Sst)mentioning
confidence: 99%